PENERAPAN ROLE PLAYING BERBANTU MEDIA BONEKA JARI DALAM MENINGKATKAN AKTIVITAS DAN PERKEMBANGAN SOSIAL PERALIHAN ANAK DARI TK KE SD - Nurul Agustin; Ivo Yuliana; Rizki Amelia Andayani (Nahdlatul Ulama University Sunan Giri Bojonegoro, Indonesia, 2022)
This study aims to increase the activity and social development of children transitioning from kindergarten to elementary school through the application of the Finger Puppet Media Assisted Role Playing Method using the Class Action Research (CAR). This research has four stages consisting of: planning, action implementation, observation and reflection. In each cycle, 1 to 4 stages are carried out and each cycle will pass through these four stages. From the research day, the students' activities in participating in learning activities using the role playing method assisted by finger puppet media reached a percentage of 55% in the first cycle and increased by 37.5% in the second cycle, obtaining a percentage of 92.5%. The results of the social development of students when participating in learning activities take place to obtain a percentage of 50%, an increase of 36.25 in the second cycle, obtaining a percentage of 86.25%. Based on these results, it can be concluded that by applying the role playing method assisted by finger puppet media, it can increase the activity and social development of children's transition from kindergarten to elementary school.